2003
DOI: 10.2105/ajph.93.9.1494
|View full text |Cite
|
Sign up to set email alerts
|

Breathless in Los Angeles: The Exhausting Search for Clean Air

Abstract: Population growth and the proliferation of roadways in Southern California have facilitated a glut of mobile air pollution sources (cars and trucks), resulting in substantial atmospheric pollution. Despite successful efforts over the past 40 years to reduce pollution, an alarming set of health effects attributable to air pollution have been described in Southern California. The Children's Health Study indicates that reduced lung function growth, increased school absences, asthma exacerbation, and new-onset ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…Air pollution in the Los Angeles area historically has been among the highest in the United States, partly due to traffic emissions in the area (43). Consistent with this, our study showed that this area has the highest MGC EPI scores in California.…”
Section: Discussionsupporting
confidence: 88%
“…Air pollution in the Los Angeles area historically has been among the highest in the United States, partly due to traffic emissions in the area (43). Consistent with this, our study showed that this area has the highest MGC EPI scores in California.…”
Section: Discussionsupporting
confidence: 88%
“…Eight sites were examined in this study, six within the Los Angeles Basin (LAB): Long Beach, Mira Loma, Upland, Riverside, Lake Arrowhead and USC; and two sites at other areas of Southern California: Alpine and Lancaster (as shown in Figure 1). Selection of the sampling sites, discussed in greater detail by Ku¨nzli et al (2003), was made on the basis of their location within the LAB and the presumed contrasting air quality (hence exposure) regimes in terms of PM and gaseous copollutants, which have differentially affected children's health.…”
Section: Methodsmentioning
confidence: 99%
“…35 The five sites selected for the current analysis are Long Beach, Glendora, Mira Loma, Upland, and Riverside. The choice of sampling sites considered in this study is based on their location within the Los Angeles Basin as well as the adverse health outcomes observed at these sites 36 attributed to air pollution. Kunzli et al 36 have studied these sites as part of the CHS investigating the long-term consequences of air pollution on the health of children.…”
Section: Methodsmentioning
confidence: 99%